Penguatan Kompetensi Guru melalui Blended Learning Bilingual: Pendekatan Teori dan Praktik dalam Kurtilas, Kurmer, dan Kurintel: Strengthening Teacher Competence through Blended Learning Bilingual: Theoretical and Practical Approaches in Kurtilas, Kurmer, and Kurintel - Laili, M Isroul (PUSAT PUBLIKASI ILMIAH SEKOLAH TINGGI AGAMA ISLAM (STAI) AL-YASINI PASURUAN, 2024)
This Community Service activity was conducted to enhance teachers’ competence in implementing a bilingual blended learning approach that aligns with the three curriculum frameworks used in Indonesia: the 2013 Curriculum (Kurtilas), the Independent Curriculum (Kurmer), and the International Curriculum (Kurintel). The program is designed in a participatory manner by involving teachers as active partners in the development of learning strategies that combine theory and practice. The method of implementing activities includes interactive workshops conducted in a blended manner (face-to-face and online), mentoring teaching practices through microteaching and team teaching sessions, and the development of digital and bilingual-based teaching tools. In the workshop, participants gained an understanding of the principles of blended learning, multicontextual curriculum structure, and bilingual pedagogy. Furthermore, teachers are guided to design lesson plans, teaching materials, and digital modules that are directly tested in the learning process. The results of the evaluation showed an increase in teachers’ ability to develop teaching tools that are adaptive to the character of students and the curriculum policies of each school. The activity also succeeded in creating a space for reflective dialogue through Forum Group Discussion (FGD), as well as encouraging the formation of a sustainable learning community across schools and levels. The expected long-term impact is the strengthening of an inclusive, technology-based, and competency-oriented learning ecosystem in the 21st century. This program makes a concrete contribution to the transformation of education at the local level with a global approach based on collaboration and innovation.